The Yin and Yang Between Plasma Glucose Levels and Cortisol Replacement Therapy in Schmidt's Syndrome - Christopher A. Newton MD; Eleni Sheehan MSN, ARNP; Kathleen Wyne MD, PhD; Kenneth Cusi MD; Julio Leey MD, MSc; Hans K. Ghayee DO (SAGE Publishing, 2017)
Objective: To illustrate how steroid replacement in adrenal insufficiency can influence the development of hypoglycemia in a patient with type 1 diabetes mellitus (T1D). Methods: We describe the case of a 36-year-old female patient with T1D and Addison's disease (Schmidt's syndrome) on multiple daily insulin injections who presented with recurrent hypoglycemia despite being on physiological replacement doses of hydrocortisone. Results: With the assistance of continuous glucose monitoring technology, a pattern of nocturnal hypoglycemia was clearly identified. The patient was taking her hydrocortisone 15 mg in the morning and 5 mg in the early afternoon. With the short half-life of oral hydrocortisone, the evening decline in plasma cortisol concentration led to an increased susceptibility to recurrent evening and nocturnal hypoglycemia. Hypoglycemic episodes were resolved when her morning hydrocortisone dose was changed and prednisolone was added to a later time in the evening. Conclusion: Patients with Schmidt's syndrome can be susceptible to nocturnal hypoglycemia with inadequate steroid replacement. Identifying patients at risk for hypoglycemia in Schmidt's syndrome provides an opportunity for precision management beyond the manipulation of antihyperglycemic agents.